Disturbance Observer Based on Sliding Mode Control for Secure Communication of Chaotic Circuits - Ming-Yuan Chiang; Van Nam Giap; Duc-Hung Pham; Van Loc Nguyen; Shyh-Chour Huang (IEEE Access, 2023)
To prevent the distortion of the data transmission, the disturbance compensation method is highly required in the communication system. Therefore, the variations of parameters on both master and slave of secure communication and attacked signals all should be compensated to remain the sent data as its after decrypting. However, to reject these unwanted signals, the time varying disturbance rejection technique is requested. The time varying disturbance observer (DO) is able to reject both low and high frequency disturbances. Furthermore, the template of the sources of the disturbances are free. To meet the goal of robust control, first, the Liu chaotic system is used to represent the master and slave systems (MSSs). Second, the disturbance observer was proposed on the side of slave system together with the controller, which used to reject the parameters variations and disturbances on the public channels. Third, the sliding mode control was proposed to synchronize the slave and master systems. Final, the mathematical stability is provided based on the Lyapunov condition. Furthermore, to show the power and effectiveness of the given theory, the circuit realization was used to conduct the theoretical analysis. The sent and received messages were mostly identical, which is used to confirm that the proposed theory on the secure communication of chaotic circuits is good both in synchronization and disturbance rejection also.